Jansky VLA S-band view of Hα emitters (HAEs) associated with a protocluster 4C23.56 at z = 2.5. Issue Volume 10:Issue S309(2014) (9th February 2015) - Lee, Minju; Suzuki, Kenta; Kohno, Kotaro; Tamura, Yoichi; Iono, Daisuke; Hatsukade, Bunyo; Nakanishi, Kouichiro; Tanaka, Ichi; Kodama, Tadayuki; Tadaki, Kenichi; Ikarashi, Soh; Ueda, Junko; et al.
Abstract: We present recent results on Karl Jansky Very Large Array (JVLA) deep S-band (2-4 GHz) observation towards a protocluster 4C23.56 at redshift z ∼ 2.5. The protocluster 4C23.56 is known to have a significant over density (∼ 5 times) of star-burst galaxies selected to be Hα line-bright by a Subaru narrow band imaging. Now we have found 25 HAEs associated with the protocluster. These starburst HAEs are likely to become massive ellipticals at z = 0 in a cluster. Various other galaxy populations also reside in this field and the fact makes the field very unique as a tool to understand galaxy formation in a over dense region. Subsequent deep 1100-μm continuum surveys by the ASTE 10-m dish have discovered that several submillimeter bright galaxies (SMGs) coincide with HAEs, suggesting HAEs undergoing dusty starbursts. As star formation rates (SFRs) of HAEs might have been underestimated, we use radio being resistant to dust extinction. We investigate the correlation between SFR1.4 GHz and SFRHα for radio index α = 0.8 to see if the correlation holds for the sources and to check the number of dusty star forming galaxies. Our final results will allow us to evaluate quantitatively how the galaxy formation channel may be different under the condition of over-densities.